Da sala de aula à sala de casa: reflexões sobre compreensão leitora em videoaulas - Brandt, Luciana Schuartz (2023)
According to the last three results of the large-scale educational evaluation, the Saeb (2017/2019/2021), which evaluates reading proficiency, there was little progress in terms of reading at the end of the initial years of Elementary School, still remaining in the basic level of reading comprehension. There are many and fundamental studies on reading in this stage of Basic Education. Therefore, the aim of this research is to assess whether the reading activities addressed in the video lessons provide, from a psycholinguistic perspective, a meaningful approach in relation to reading processing and awareness of metacognitive strategies. For this purpose, two didactic sequences were selected from video classes on TV Escola Curitiba, from the 5th year, from the Municipal Secretariat of Education of Curitiba, to answer, in a contextual and detailed way, the guiding question of this project: during the video classes, the materials used had the potential to provide reading comprehension, considering aspects related to reading strategies and proficiency levels? The study is supported by the psycholinguistic aspects of Solé (1998) as it considers essential prior knowledge (encyclopedic, linguistic, discursive), as well as cognitive and metacognitive memory competence and reading strategies (before, during and after). The cognitive and socio cognitive approach to reading from the perspective of Kleiman (1989; 2004; 2016), Kato (1990), among others, will also be present in the discussion. Parameter documents (curriculum from Curitiba and BNCC) are also necessary to support the research. For the realization of this theoretical-pedagogical path, the study will have a qualitative approach, of an interpretative character, since the intention is to investigate the data and understand them in a certain socio-historical-social context, descriptively, as well as to reflect on the ways of production of scientific knowledge acquired throughout the research (MOITA LOPES, 1994). The data will be evaluated from the mapping and analysis of the reading strategies used in the selected video lessons. Based on these reflections, we intend to assess whether or not the way classes were organized contributes to the development of reading comprehension in 5th grade students from a psycholinguistic perspective. The results obtained from the research prove that there are contributions and potentialities in video classes in relation to reading comprehension, especially for the training of teachers working in the early years, in order to make their students critical and proficient readers, as well as to encourage discussions about reading in Teaching Fundamental.